Drug repurposing for rare: progress and opportunities for the rare disease community - Anneliene Hechtelt Jonker; Anneliene Hechtelt Jonker; Daniel O’Connor; Daniel O’Connor; Maria Cavaller-Bellaubi; Maria Cavaller-Bellaubi; Christine Fetro; Christine Fetro; Maria Gogou; Maria Gogou; Peter A. C. ’T Hoen; Peter A. C. ’T Hoen; et al. (Frontiers in Medicine, 2024)
Repurposing is one of the key opportunities to address the unmet rare diseases therapeutic need. Based on cases of drug repurposing in small population conditions, and previous work in drug repurposing, we analyzed the most important lessons learned, such as the sharing of clinical observations, reaching out to regulatory scientific advice at an early stage, and public-private collaboration. In addition, current upcoming trends in the field of drug repurposing in rare diseases were analyzed, including the role these trends could play in the rare diseases’ ecosystem. Specifically, we cover the opportunities of innovation platforms, the use of real-world data, the use of artificial intelligence, regulatory initiatives in repurposing, and patient engagement throughout the repurposing project. The outcomes from these emerging activities will help progress the field of drug repurposing for the benefit of patients, public health and medicines development.